2015
DOI: 10.1590/1807-3107bor-2015.vol29.0048
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behavior of dentists in a dental school regarding toothbrush disinfection

Abstract: The aim of this study was to evaluate the knowledge and behavior of dentists regarding toothbrush disinfection. This study included 147 dentists (88 women and 59 men) who were actively employed at a dental school in Ankara, Turkey. Participants were asked to fill out a standard questionnaire, which contained questions regarding their demographics, brushing habits, toothbrush storage and disinfection habits, toothpaste use, knowledge about toothbrush disinfection, and whether they advised their patients about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 19 publications
(35 reference statements)
0
26
3
1
Order By: Relevance
“…From Table 1, majority of the students (53.75%) preferred storing their toothbrushes in the bedroom to anywhere else. This does not tally with the findings of a similar study that indicated 53.1% of Turkish dentists preferring to store their oral hygiene aid in the bathroom to anywhere else [13]. This may depend on whether the individual takes his/ her breakfast before or after bath.…”
Section: Discussioncontrasting
confidence: 73%
“…From Table 1, majority of the students (53.75%) preferred storing their toothbrushes in the bedroom to anywhere else. This does not tally with the findings of a similar study that indicated 53.1% of Turkish dentists preferring to store their oral hygiene aid in the bathroom to anywhere else [13]. This may depend on whether the individual takes his/ her breakfast before or after bath.…”
Section: Discussioncontrasting
confidence: 73%
“…The toothbrush has a significant role to reintroduce microorganisms into the oral cavity [ 27 , 28 ]. Since it is not feasible to change the toothbrush every day, it is recommended as a sound practice to change the toothbrush at least after every three months [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that the majority of people just rinse the brushes with plain water and then dry it to prevent contamination with potential disease-producing bacteria fungi and viruses. [32,33] In a survey-based study conducted by Peker et al [34] to assess knowledge of toothbrush hygiene among dental students, 62.6% of the respondents reported that they did not know about toothbrush disinfection and did not disinfect their toothbrushes. It is advisable to dip the toothbrushes into an antiseptic mouthwash a few minutes after rinsing with water after each use.…”
Section: Standard Oral Hygiene Practicesmentioning
confidence: 99%